Correction: A microphysiological early metastatic niche on a chip reveals how heterotypic cell interactions and inhibition of integrin subunit β3 impact breast cancer cell extravasation. Issue 6 (9th March 2021) - Crippa, Martina; Bersini, Simone; Gilardi, Mara; Arrigoni, Chiara; Gamba, Sara; Falanga, Anna; Candrian, Christian; Dubini, Gabriele; Vanoni, Marco; Moretti, Matteo
Abstract : Correction for 'A microphysiological early metastatic niche on a chip reveals how heterotypic cell interactions and inhibition of integrin subunit β3 impact breast cancer cell extravasation' by Martina Crippa et al., Lab Chip, 2021, DOI: ; 10.1039/d0lc01011a .